Adolescent Literature Revisited after Four Years - Arizona English Teachers Association, Tempe; Donelson, Ken; Arizona English Teachers Association, Tempe ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
The articles collected in this bulletin survey a wide range of topics concerning adolescent literature. Some of the titles included are "Seven Myths about Adolescent Literature" (Paul B. Janeczko), "The Book as Enemy" (Thomas Weaver), "Popular Non-Fiction Titles for Adolescents" (Noma Russell), "Values and Paperback Power" (Nel Ward), "An Approach to Sex Roles in Secondary Literature" (Dianne Bettis), and "An Annotated Bibliography of Recent Fiction about Native Americans" (Norma Inkster). Other articles examine the significance of death in adolescent literature; provide discussions of fantasy literature, literature and television, and student attitudes toward reading; interpret the role of the teacher; and research the habits and interests of adolescent readers. (KS)
Availability: National Council of Teachers of English, 1111 Kenyon Road, Urbana, Illinois 61801 (Stock No. 00546, $4.95 non-member, $4.50 member).
Educational level discussed: Secondary Education.
Arizona English Bulletin, v18 n3 Entire Issue April 1976.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adolescent Literature; Adolescents; Annotated Bibliographies; Bibliographies; Interest Research; Reading Habits; Reading Instruction; Reading Interests; Reading Materials; Secondary Education; Student Attitudes; Journal Articles